2017
DOI: 10.1177/1352458517691149
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between white matter fiber damage and gray matter perfusion in large-scale functionally defined networks in multiple sclerosis

Abstract: Overall, GM node perfusion was associated with severity rather than extent of WM network damage, supporting a primary etiology of GM hypoperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Our previous article (Figley et al, 2015) demonstrated how these functionally-defined white matter atlases can be used for voxel-wise and/or ROI-based analyses to examine relationships between structural measures throughout functionally-defined tracts or networks, and the initial white matter atlases have already proven useful for examining network-specific structural differences related to body composition (Figley et al, 2016) and Multiple Sclerosis (Ma et al, 2017). However, it is our hope that the addition of these new networks—related to different domains (e.g., language, vision, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous article (Figley et al, 2015) demonstrated how these functionally-defined white matter atlases can be used for voxel-wise and/or ROI-based analyses to examine relationships between structural measures throughout functionally-defined tracts or networks, and the initial white matter atlases have already proven useful for examining network-specific structural differences related to body composition (Figley et al, 2016) and Multiple Sclerosis (Ma et al, 2017). However, it is our hope that the addition of these new networks—related to different domains (e.g., language, vision, etc.…”
Section: Discussionmentioning
confidence: 99%